2022
DOI: 10.1186/s12882-022-02777-9
|View full text |Cite
|
Sign up to set email alerts
|

Duration of delayed graft function and its impact on graft outcomes in deceased donor kidney transplantation

Abstract: Background There is controversy regarding the impact of delayed graft function (DGF) on kidney transplant outcomes. We hypothesize that the duration of DGF, rather than DGF itself, is associated with long-term kidney graft function. Methods We analyzed all deceased donor kidney transplants (DDKT) done at our center between 2008 to 2020. We determined factors associated with DGF duration. DGF duration was assessed at three 14-day intervals: < 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…These concerns likely limit broader utilization of kidneys at risk for DGF, such as those coming from AKI, high KDPI and DCD donors (8,16). More recent studies have suggested that there is in fact significant heterogeneity within DGF (1)(2)(3)(17)(18). In this cohort, we found that the majority of recipients with DGF had excellent patient and graft survival and lower graft survival was noted only for those with ≥2 readmissions; this finding remained true when accounting for death-censored graft loss (Figure 2) (14-15).…”
Section: Discussionmentioning
confidence: 99%
“…These concerns likely limit broader utilization of kidneys at risk for DGF, such as those coming from AKI, high KDPI and DCD donors (8,16). More recent studies have suggested that there is in fact significant heterogeneity within DGF (1)(2)(3)(17)(18). In this cohort, we found that the majority of recipients with DGF had excellent patient and graft survival and lower graft survival was noted only for those with ≥2 readmissions; this finding remained true when accounting for death-censored graft loss (Figure 2) (14-15).…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged CIT is closely associated with DGF 1 . The true clinical significance of DGF on transplant outcomes remains debated although its impact on resources and financial cost is relatively well established 8,22–27 . It is likely that concerns for clinical outcomes, in addition to the increased incidence and duration of DGF, may limit broader use of kidney allografts with longer CIT 25–27 .…”
Section: Discussionmentioning
confidence: 99%
“…1 The true clinical significance of DGF on transplant outcomes remains debated although its impact on resources and financial cost is relatively well established. 8,[22][23][24][25][26][27] It is likely that concerns for clinical outcomes, in addition to the increased incidence and duration of DGF, may limit broader use of kidney allografts with longer CIT. [25][26][27] Difficulty in coordinating logistical transportation is yet another risk factor for prolonging CIT, particularly for difficult-to-place kidneys that have incurred late allocation declines.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our study, a few studies showed no association between DGF and BK viremia. 31,32 Budhiraja et al 33 found that among 1714 DDKTs, of whom 59.4% had DGF, the rate of BK viremia within the first year of the transplant was not significantly different between those with and without DGF (P = 0.24); 116 (16.7%) in no DGF, 106 (14.2%) in DGF lasted ≤14 d, 31 (14.3%) in DGF lasted 15 to 28 d, and 4 (7.7%) in DGF lasted >28 d. A few studies assessed the associations of prolonged cold ischemia time and DCD kidneys, which are also important risk factors for DGF, and found an increased risk of BK replication likely because of ischemiareperfusion injury. 34,35 There are mixed reports assessing the association between DGF and CMV.…”
Section: Discussionmentioning
confidence: 99%